2020
DOI: 10.1007/s42844-020-00017-3
|View full text |Cite
|
Sign up to set email alerts
|

Resilience During Pregnancy: How Early Life Experiences are Associated with Pregnancy-Specific Stress

Abstract: High levels of maternal pregnancy-specific stress are associated with an increased risk for adverse birth outcomes as well as anxiety and depression symptoms during and following pregnancy. There is evidence that early childhood experiences play an important role in maternal psychological health and well-being and may be important for shaping maternal vulnerability to pregnancy-specific stress. The current study examined the link between both maternal adverse childhood experiences (ACEs) and protective and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…Thus, our findings are in line with those provided by structural equation models in other studies. For example, they support those found by Armans et al ( 2020 ), who showed that resilience negatively influenced pregnancy-specific stress, or those found by Peñacoba-Puente et al ( 2016 ), which demonstrated how pregnancy worries had an impact on anxiety symptoms before the pandemic. The results provided by this model showed that resilience also acts as a buffering factor in relation to stress, pregnancy worries and anxious symptoms in women during their pregnancy before the COVID-19, and not only in times of crisis or great adversity.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Thus, our findings are in line with those provided by structural equation models in other studies. For example, they support those found by Armans et al ( 2020 ), who showed that resilience negatively influenced pregnancy-specific stress, or those found by Peñacoba-Puente et al ( 2016 ), which demonstrated how pregnancy worries had an impact on anxiety symptoms before the pandemic. The results provided by this model showed that resilience also acts as a buffering factor in relation to stress, pregnancy worries and anxious symptoms in women during their pregnancy before the COVID-19, and not only in times of crisis or great adversity.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, several investigations have discovered a negative association between resilience and anxiety during pregnancy (Lubián López et al, 2021 ), and between resilience towards stress and anxiety in other populations at the time of the pandemic (Braun-Lewensohn et al, 2021 ; Satici et al, 2020 : Wang et al, 2021 ). Additionally, previous researches carried out before the pandemic have proven the protective role of resilience regarding these variables in the perinatal stage (Armans et al, 2020 ; García-León et al, 2019 ).…”
Section: Introductionmentioning
confidence: 89%
“…It is important to note that our examination of PACEs was based on a cumulative factor, adding up the PACEs reported on, rather than examining the factors individually. Several recent studies indicate that cumulative positive experiences in childhood should be considered when examining resilience (Armans et al, 2020 ; Bethell et al, 2019 ; Narayan et al, 2020 ; Yamaoka & Bard, 2019 ). For example, Bethell and colleagues found a dose-response between positive childhood experiences and adult mental and relational health, “analogous to the cumulative effects of multiple ACEs” in a large, retrospective study of adults (Bethell et al, 2019 , p. 8).…”
Section: Discussionmentioning
confidence: 99%
“…For example, PACEs have been found to act as a buffer between negative parenting attitudes and adverse childhood experiences 2,8 . Similarly, PACEs have been associated with greater resilience and less stress during pregnancy (e.g., future worries about parenting 9 ). Taken together, these findings suggest that PACEs buffer the deleterious effects of ACEs on adult functioning and mental health.…”
Section: Protective and Compensatory Childhood Experiences And Their ...mentioning
confidence: 99%